1982
DOI: 10.3109/10826088209071021
|View full text |Cite
|
Sign up to set email alerts
|

Stereotyping as a Negative Factor in Substance Abuse Treatment

Abstract: Sixty addicts, health professionals, and counseling students were administered the Internal-External Locus of Control Test and the Multiple Affect Adjective Check List to determine if stereotypes exist between the subject groups, the nature of the stereotypes, and if educational level alters the stereotypes. The findings demonstrated gross misperception of addict clients by the health professionals and students, particularly toward psychotic and hostile dimensions. Educational level was found to improve the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The drug addiction module is a one-page article outlining common myths and parallel facts regarding drug addiction (see Appendix II). A drug addiction module was chosen for the control condition based on the premise that drug addiction and treatment commonly attract stereotypes and misperceptions (Cohen, Griffin, & Wiltz, 1982). It was taken from the website for the National Institute on Drug Addiction (Leshner, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The drug addiction module is a one-page article outlining common myths and parallel facts regarding drug addiction (see Appendix II). A drug addiction module was chosen for the control condition based on the premise that drug addiction and treatment commonly attract stereotypes and misperceptions (Cohen, Griffin, & Wiltz, 1982). It was taken from the website for the National Institute on Drug Addiction (Leshner, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the evidence that LoC is associated with the use/abuse of substances [26], and in contrast with more widely studied behaviours such as cessation and abstinence in adults, data about the relationship between LoC orientation and tobacco and/or alcohol use in young adults is limited. The studies that have examined this have reported that adolescent smokers with a higher nicotine dependence and individuals with greater alcohol consumption, had a more external LoC; however, all of these studies have been limited by relatively small sample sizes and/or by using cross-sectional designs that do not allow to analyse behaviour over a period of time [27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%